2016
DOI: 10.1016/j.jamcollsurg.2016.08.541
|View full text |Cite
|
Sign up to set email alerts
|

Neoadjuvant Systemic Therapy Use for Younger Patients with Breast Cancer Treated in Different Types of Cancer Centers Across the United States

Abstract: Background Multiple clinical trials have shown that neoadjuvant systemic therapy has a benefit in women who are borderline lumpectomy candidates and in those with locally-advanced breast cancers by reducing the mastectomy rate and making inoperable tumors operable. The study aim was to examine the patterns of neoadjuvant chemotherapy and endocrine therapy use among younger women in the US treated at different types of cancer centers. Study Design Data from the National Cancer Data Base for 118,086 women youn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
22
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 20 publications
(27 reference statements)
5
22
1
Order By: Relevance
“…In our study, 22.92% of female patients received chemotherapy prior to surgery, slightly higher compared to 17.4–17.7% in the US, but lower than the 35.2% of patients in South Africa . The use of NACT is higher in younger than in older patients who do not commonly have contradictions, which is also consistent with the results of large studies conducted in Asia and the US . In our study, the proportion of patients treated with NACT before RM (35.15%) and MRM (24.87%) was higher than BCS (22.02%), and patients with metastatic tumors (33.88%) most frequently receive NACT compared to other subgroups.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In our study, 22.92% of female patients received chemotherapy prior to surgery, slightly higher compared to 17.4–17.7% in the US, but lower than the 35.2% of patients in South Africa . The use of NACT is higher in younger than in older patients who do not commonly have contradictions, which is also consistent with the results of large studies conducted in Asia and the US . In our study, the proportion of patients treated with NACT before RM (35.15%) and MRM (24.87%) was higher than BCS (22.02%), and patients with metastatic tumors (33.88%) most frequently receive NACT compared to other subgroups.…”
Section: Discussionsupporting
confidence: 89%
“…71 The use of NACT is higher in younger than in older patients who do not commonly have contradictions, which is also consistent with the results of large studies conducted in Asia and the US. 68,72,73 In our study, the proportion of patients treated with NACT before RM (35.15%) and MRM (24.87%) was higher than BCS (22.02%), and patients with metastatic tumors (33.88%) most frequently receive NACT compared to other subgroups. Studies have shown that NACT did convert mastectomy patients to candidates for BCS and reduced the number of dissected lymph nodes.…”
Section: Discussionmentioning
confidence: 58%
“…Several large studies in the USA, including one of >250,000 patients, found that NACT was administered to 17%–36% of patients with nonmetastatic breast cancer. 39 41 Similar to patients in our cohort, those in US samples were more likely to receive NACT if they had large tumors or late-stage disease. Most treatment guidelines call for NACT in patients with locally advanced breast cancer precisely because it can shrink inoperable tumors, facilitate definitive surgery, and increase the rates of breast conservation.…”
Section: Discussionmentioning
confidence: 54%
“…NT is more frequent in tumors with negative receptors (14.8%), less than the 23.5% reported by Mougalian et al 18 The multivariate analysis confirmed higher values for subtype luminal B (OR 1.87) and for triple-negative (OR 1.88); Mohiuddin et al 13 reports similar values (OR 1.50 and 1.70, respectively). NT is less frequent in lobular morphology (OR 0.82) and in mixed morphology (0.35), in line with what Mohiuddin et al 13 reported. A positive correlation for grading was found only for unknown forms (OR 8.86), while nonsignificant excesses were found for grades 2 and 3, unlike what other studies have reported.…”
Section: Discussionmentioning
confidence: 71%